2011
DOI: 10.1093/jac/dkr442
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus intermittent infusion of vancomycin for the treatment of Gram-positive infections: systematic review and meta-analysis

Abstract: Our meta-analysis suggests that administration of vancomycin for the treatment of Gram-positive infections by CoI is associated with a significantly lower risk of nephrotoxicity when compared with InI of the drug. RCTs are needed to define the impact on mortality rate and on the pharmacodynamic activity in terms of AUC/MIC ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
137
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 33 publications
1
137
0
4
Order By: Relevance
“…A clinical trial in intensive care unit (ICU) patients did not show better outcome using CI but it was associated with an earlier achievement of desired trough concentrations, and concentrations were more stable over time [56]. In addition, a meta-analysis showed decreased nephrotoxicity with CI [57]; however, patients included in some of the articles were outpatients and so with a lower risk of developing nephrotoxicity. A recent article including a large cohort of ICU patients receiving vancomycin by CI showed a rate of nephrotoxicity of 24%, where the mean concentration of vancomycin within the first 3 days and the duration of treatment were independently associated with a higher risk of nephrotoxicity [58].…”
Section: Heteroresistancementioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial in intensive care unit (ICU) patients did not show better outcome using CI but it was associated with an earlier achievement of desired trough concentrations, and concentrations were more stable over time [56]. In addition, a meta-analysis showed decreased nephrotoxicity with CI [57]; however, patients included in some of the articles were outpatients and so with a lower risk of developing nephrotoxicity. A recent article including a large cohort of ICU patients receiving vancomycin by CI showed a rate of nephrotoxicity of 24%, where the mean concentration of vancomycin within the first 3 days and the duration of treatment were independently associated with a higher risk of nephrotoxicity [58].…”
Section: Heteroresistancementioning
confidence: 99%
“…Promoting higher doses promotes accepting nephrotoxicity, which requires an assessment of the level of concern and appropriate risk assessment [57]. An established link exists between vancomycin levels and renal toxicity, with van Hal et al among others showing that if the vancomycin trough is >20 mg/L toxicity is 33%, and if it is <20 mg/L then toxicity is 20%, so levels ought to be measured [28,64].…”
Section: Heteroresistancementioning
confidence: 99%
“…However, these higher doses are associated with increased incidence of nephrotoxicity. Continuous infusion has been associated with lower rates of nephrotoxicity (nephrotoxicity threshold around 28 μg/mL), higher steady state concentration, faster achievement of target concentrations, less variability in serum concentrations, and simpler AUC assessment, compared with intermittent dosing [5]; however, there is no evidence of higher effectiveness of the continuous regimen [6].…”
mentioning
confidence: 99%
“…A systematic review and meta-analysis of intermittent vancomycin dosing regimens identified trough values in excess of 15 mg/L and longer duration of vancomycin administration as independent risk factors for (25,26). Overall, a trough value in excess of 15 mg/L (relative to a trough value below 15 mg/L) was associated with an increased odds ratio of 2.67 for nephrotoxicity (25).…”
Section: The Pyrrhic Victorymentioning
confidence: 99%